Effects of 24-hour sleep deprivation on heart rate regulation in nurses - I. M. Voronin; I. A. Kirillova (Кардиоваскулярная терапия и профилактика)
Aim. To assess heart rate variability (HRV) in response to 24-hour sleep deprivation (SD) among nurses with various work schedules.Material and methods. The study included 24 healthy nurses from cardiac hospital departments (mean age 35,5 6,5 years). HRV was registered in the morning: in the main group – before and after 24 hours on duty, in the controls – before work and the next day, after a normal night sleep. HRT was analyzed by a time-frequency method: spectral powers for high, low, and very low frequencies (HF, LF, and VLF, respectively) were measured, as well as  LF/HF.Results. In the main group, background LF/HF was significantly higher than in the controls (р=0,0410). 24-hour SD was associated with substantial decrease in LF power (р=0,0267), with unchanged HF power. Consequently, LF/HF reduced significantly (р=0,0150).Conclusion. 24-hour SD reduced activity of sympathetic regulation of chronotropic cardiac function and changed autonomic balance towards relative increase of parasympathetic effects on heart rate. Chronic SD enhanced background sympathetic activity and reduced its adaptive potential, which could be one of the factors of increased cardiovascular morbidity and mortality as a result of working shifts.